Cancer treatment and survivorship statistics, 2025 - Nikita Sandeep Wagle; Leticia Nogueira; Theresa P. Devasia; Angela B. Mariotto; K. Robin Yabroff; Farhad Islami; Ahmedin Jemal; Rick Alteri; Patricia A. Ganz; Rebecca L. Siegel (CA: A Cancer Journal for Clinicians, 2025)
Abstract The number of people living with a history of cancer in the United States continues to rise because of the growth and aging of the population as well as improved survival through advances in early detection and treatment. To assist the public health community serve the needs of these survivors, the American Cancer Society and the National Cancer Institute collaborate triennially to estimate cancer prevalence in the United States using data from the Surveillance, Epidemiology, and End Results cancer registries, the Centers for Disease Control and Prevention's National Center for Health Statistics, and the United States Census Bureau. In addition, cancer treatment patterns are presented from the National Cancer Database along with a brief overview of treatment‐related side effects. As of January 1, 2025, about 18.6 million people were living in the United States with a history of cancer, and this number is projected to exceed 22 million by 2035. The three most prevalent cancers are prostate (3,552,460), melanoma of the skin (816,580), and colorectum (729,550) among males and breast (4,305,570), uterine corpus (945,540), and thyroid (859,890) among females. About one half (51%) of survivors were diagnosed within the past 10 years, and nearly four fifths (79%) were aged 60 years and older. Racial differences in treatment in 2021 were common across disease stage; for example, Black people with stage I‐II lung cancer were less likely to undergo surgery than their White counterparts (47% vs. 52%). Larger disparities exist for rectal cancer, for which 39% of Black people with stage I disease undergo proctectomy or proctocolectomy compared to 64% of their White counterparts. Targeted, multi‐level efforts to expand access to high‐quality care and survivorship resources are vital to reducing disparities and advancing support for all survivors of cancer.